Carbon Ion Beam Boost Irradiation in Malignant Tumors of the Nasal Vestibule and the Anterior Nasal Cavity as an Organ-Preserving Therapy - Eberle, Fabian; Engenhart-Cabillic, Rita; Schymalla, Markus M.; Dumke, Christoph; Schötz, Ulrike; Subtil, Florentine S.B.; Baumann, Kilian-Simon; Stuck, Boris A.; Langer, Christine; Jensen, Alexandra D.; Hauswald, Henrik; Lautenschläger, Stefan (Frontiers in Oncology, 2022)
Background: Surgery and radiotherapy are current therapeutic options for malignant tumors involving the nasal vestibule. Depending on the location, organ-preserving resection is not always possible, even for small tumors. Definitive radiotherapy is an alternative as an organ-preserving procedure. Carbon ion beam radiotherapy offers highly conformal dose distributions and more complex biological radiation effects eventually resulting in optimized normal tissue sparing and improved outcome. Aim of the current study was to analyze toxicity, LC and OPS after irradiation of carcinoma of the nasal vestibule with raster scanned CIRT-B combined with VMAT with photons. Methods: Between 12/2015 and 05/2021 21 patients with malignant tumors involving the nasal vestibule were irradiated with CIRT-B combined with VMAT and retrospectively analyzed. Diagnosis was based on histologic findings. 17 patients had SCC and 4 had other histologies. In this series 10%, 67% and 24% of patients had Wang stage 1, 2 and 3 tumors, respectively. 3 patients had pathologic cervical nodes on MRI. Median CIRT-B dose was 24 Gy (RBE), median VMAT dose was 50 Gy. All patients with pathologic cervical nodes received photon SIB up to a median dose of 62.5 Gy to the pathological lymph nodes. 8 patients received cisplatin chemotherapy. All patients received regular follow-up imaging after irradiation. Kaplan-Meier estimation was used for statistical assessment. Results: The median follow-up after irradiation was 18.9 months. There were no common toxicity criteria grade 5 or 4 adverse events. 20 patients showed grade 3 adverse events mainly on skin and mucosa. All patients were alive at end of follow-up. The median OPS after treatment was 56.5 months. The 6- and 24-months OPS was 100% and 83.3%, respectively. All local recurrences occurred within 12 months after radiotherapy. The median PFS after treatment was 52.4 months. The 6- , 12- and 24-months PFS rates were 95%, 83.6% and 74.3%, respectively. Conclusion: CIRT-B combined with VMAT in malignant tumors of the nasal vestibule is safe and feasible, results in high local control rates and thus is a good option as organ-preserving therapy. No radiation-associated grade 4 or 5 acute or late AE were documented.